Effect of Fetal Membrane-Derived Mesenchymal Stem Cell Transplantation in Rats With Acute and Chronic Pancreatitis. Issue 5 (May 2016) - Kawakubo, Kazumichi; Ohnishi, Shunsuke; Fujita, Hirotoshi; Kuwatani, Masaki; Onishi, Reizo; Masamune, Atsushi; Takeda, Hiroshi; Sakamoto, Naoya
Abstract : Objectives: Mesenchymal stem cells (MSCs) are a valuable cell source in regenerative medicine and can be isolated from fetal membranes (FMs), particularly amniotic membranes. We investigated the effect of rat FM-derived MSCs (rFM-MSCs) and human amnion-derived MSCs (hAMSCs) on the inflammatory reaction in vitro and therapeutic effects in rats with acute and chronic pancreatitis. Methods: Effect of rFM-MSCs or hAMSC-conditioned medium was investigated in vitro. Acute pancreatitis was induced by intraductal injection of 4% taurocholate, and rFM-MSCs were transplanted intravenously. Chronic pancreatitis was induced by intravenous injection of 5 mg/kg dibutyltin dichloride, and hAMSCs were transplanted intravenously. Results: The inflammatory reaction of macrophages induced by lipopolysaccharide and trypsin was significantly suppressed by rFM-MSC coculture. Pancreatic acinar cell injury induced by cerulein was significantly ameliorated by hAMSC-conditioned medium. Pancreatic stellate cell activation induced by tumor necrosis factor-α was significantly decreased by hAMSC-conditioned medium. Transplantation of rFM-MSCs significantly reduced the histological score and infiltration of CD68-positive macrophages in the rat pancreas. The hAMSC transplantation significantly decreased the expression of MCP-1 and attenuated the downregulation of amylase expression in the pancreas. Conclusions: Transplantation of FM-MSCs and AMSCs suppressed the inflammatory reaction of acute and chronic pancreatitis in rats.